Clomiphene for hypogonadism complicated by polycythemia. Issue 1 (2nd January 2019) - Francisco, Roshirl; Jaroudi, Sarah; Murtaza Ali, Mariam; Frost, Jill; Chemitiganti, Rama; Peiris, Alan N.
Abstract: Male hypogonadism is associated with poor sexual function. Testosterone therapy via the intramuscular route is the preferred treatment but is associated with secondary polycythemia. We report a patient in whom clomiphene citrate improved hypogonadal symptoms and restored normal free testosterone levels. Clomiphene is inexpensive and can be given orally in secondary hypogonadism. Clomiphene citrate is a promising alternative in patients who develop secondary polycythemia with testosterone.